Analysis Of The Use Of White Sweet Potato Flour On The Quality Of Pineapple - Shafira, Ersa; Gusnita, Wiwik; Holinesti, Rahmi; Anggraini, Ezi (Jurnal Pendidikan Tata Boga dan Teknologi, 2023)
Nastar is a semicircular round pastry with a diameter of 2 cm, made from a dough of wheat flour, butter, and eggs with pineapple jam filling. White sweet potatoes are more directed to the development of flour and starch because the color of the flour produced is more like wheat germ, and brightly colored sweet potatoes tend to have better starch levels. So that white sweet potato flour can be used in making nastar. This study aims to analyze the effect of using white sweet potato flour as much as 15%, 30%, and 45% on the quality of the shape, color, aroma, texture and taste of pineapple produced. This type of research is a pure experiment with the Complete Randomized Design method. The data used were primary data obtained directly from 3 expert panelists by filling in the organoleptic test format on the quality of pineapple with the influence of the use of white sweet potato flour. The data obtained is then tabulated in tabular form and carried out Variance Analysis (ANAVA), if Fh>Ft then continued with the Duncan Test. The results showed that there was a significant influence of the use of 15%, 30%, and 45% white sweet potato flour on the quality of color (golden yellow at the top and brownish yellow at the bottom), aroma (fragrant), and nastar taste (sweet taste and distinctive taste of sweet potatoes). The best result of the pineapple quality test with the use of white sweet potato flour is 15%.